Proteolytic Activity Attenuates the Response of Endothelial Cells to Fluid Shear Stress - Altshuler, Angelina E. (2012)
Recent evidence indicates that several experimental pathophysiological conditions are associated with elevated protease activity in plasma, which impacts endothelial function. We hypothesize that extracellular structures bound to the endothelial cell (EC) membrane may be degraded by proteolytic activity and cause the cells to respond abnormally to physiological shear stress (12 dyn/cm(2)). To test this hypothesis, cultured bovine aortic endothelial cells (BAECs) were exposed to low levels of a serine protease, trypsin. Extracellular mechanosensor densities of the glycocalyx and vascular endothelial growth factor receptor 2 (VEGFR-2) were determined. Metabolic dysfunction was tested by examining insulin receptor and glucose uptake levels. Protease treatment impaired the cells’ ability to align in the direction of fluid flow after 12 hours of shear stress; however, cells realigned after an additional 12 hours of shear stress with protease inhibition. Proteases caused reduction in the densities of glycocalyx, VEGFR-2, and insulin receptor in static and shear conditions, except for static VEGFR-2 cells. Under static conditions, protease-treated endothelial cells had reduced glucose uptake compared to untreated controls. Under shear, however, glucose uptake for protease-treated BAECs was greater than untreated controls. In conclusion, protease activity in plasma alters the exofacial membrane components of ECs and may interfere with mechanotransduction.